Rejoinder - Schatz, Sayre P. (Quarterly Journal of Economics, 1965)
Journal Article Rejoinder Get access Sayre P. Schatz Sayre P. Schatz University of Ibadan Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 79, Issue 2, May 1965, Pages 246–247, https://doi.org/10.2307/1880629 Published: 01 May 1965